Ответ:
формулы - (а-в)²=а²-ав+в²
- (а+в)²=а²+ав+в²
не забывай - на - даёт +
Д=в²-4*а*с
х₁=![\frac{-b-\sqrt{D} }{2*a} \frac{-b-\sqrt{D} }{2*a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b-%5Csqrt%7BD%7D%20%7D%7B2%2Aa%7D)
x₂=![\frac{-b+\sqrt{D} }{2*a} \frac{-b+\sqrt{D} }{2*a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B%5Csqrt%7BD%7D%20%7D%7B2%2Aa%7D)
Пошаговое объяснение:
1)(11-х)²=121-22х+х²
Д=484-4*121*1=0(значит 1 корень)
х=
=11
2)(2х+0,5)²=4х²+2х+0,25
Д=4-4*4*0,25=0(1 корень)
х=
=-
=-
=-0,25
3)(-3а+2в)²=-9а²-12ав+4в²
4)(а²+в³)²=а⁴+2а²в³+в⁶
5)(у+15)²=у²+30у+225
Д=900-4*1*225=0(1 корень)
х=
=-15
6)(5х-0,2)²=25х²-2х+0,04
Д=4-4*25*0,04=0(1 корень)
х=
=
=0,04
7)(-2а+7в)²=4а²-28ав+49в²
8)(а³+в⁴)²=а⁶+2а³в⁴+в⁸